Оптимізація прогресу команди та технологій управління проектами в IT-компаниях на платформі Jira - Добудько, А. М. (ХНУРЕ, 2024)
Jira is a popular project management tool can help organize and track team tasks, progress, and collaboration. With Jira, you can effectively manage your team's workflows. To do this, you need to configure and optimize workflows in Jira according to the needs and goals of the team.
Keywords: платформа Jira; правління завданнями; візуалізація прогресу